Progress in study of Cannabis sativa leaves extracts without psychotropic cannabinoids in animal model of neuropathic pain (Journal of Medical Science, 2014)
Neuropathic pain is a type of chronic pain caused by a lesion or disease of the somatosensory nervous system. Current therapy for this pain includes the use of pharmacological and nonpharmacological methods but due to the fact that a lot of therapy does not produce the analgesic results, it is necessary to search for new and more effective pharmacological strategy in relief of this type of pain. One of the interesting natural sources of compounds against this type of pain is extract of Cannabis sativa without psychotropic cannabinoids. Medicinal properties of C. sativa have been explored for centuries. It is well established that active compounds of this herb act through two cannabinoid receptors (CB1, CB2) as endocannabinoid system in the central nervous system. The present review addresses the recent advances in the study of pharmacological mechanisms on cellular and receptor level underlying non-hallucinogenic cannabinoid analgesic effect. In recent years, results of studies allow to state that special plant extract of C. sativa (without psychotropic cannabinoids) may be a promising source of drug used to relieve neuropathic pain.